La psicopatia in ambito giuridico, diagnostico e clinico-terapeutico - Fargnoli, Francesco; Zanobini, Valentina; Belli, Simone (Il sogno della farfalla, 2019)
Over the last few years legal and clinical issues have arisen in Italy, stimulating a debate on the real nature of psychopathy. The implementation of law n. 81 (2014) determined the final closure of the OPG (judicial psychiatric hospitals) with the objective of realizing an equal treatment for mentally ill patients charged for crimes as for the other psychiatric patients. However, many authors believe that the so-called psychopathic patients, who since the verdict of Court of Appeal Sezioni Unite “Raso” in 2005 cannot be considered imputable, would be better managed in a penitentiary environment or in high security facilities rather than in the existing REMS (residencies for safety measure executions). Paradoxically law n. 81, which is ideologically in line with law n. 180 (1978), leads the psychiatrist back to the role of vigilant and caretaker as it was before Basaglia’s reform. By critically tracing the historical evolution of the concept of psychopathy, the authors propose a different perspective retrieving classical psychopathology and diagnosis as the basis of a psychiatry model not willing to abdicate its medical role.